Educação Infantil e gênero: um estudo das relações de gênero presente nas brincadeiras infantis - Barbosa, Tainara Pinheiro (Universidade Federal do Tocantins, 2024)
The present work aims to discuss gender relations present in children's games and highlight the importance of the debate on gender in the school environment and in other spaces so that it can be known and recognized that there are unequal relations between Men/Women and Boys/ Girls and fight them, aiming to build a less unequal society in relation to this issue. Therefore, with the aim of contributing to the production of knowledge on this topic, this investigation was carried out through an analysis of the trajectory of the elaboration of the concept of gender, as well as the relationship between children's games and the constitution of gender roles in childhood. To this end, this study was carried out based on exploratory and bibliographical research, based on authors and researchers who discuss the issue of gender in early childhood education. It was thus established that gender is historically and culturally constructed based on individual and collective experiences. In this way, games and toys in childhood provide opportunities for the construction of social roles and influence children's future lives. It was also noticed that investigating gender and sexuality is still a taboo in our society. Therefore, it is important that teachers contribute to an education that includes everyone and that combats gender inequality from childhood.